Integrating Financial Capability into Government Cash Transfer Programs - World Bank Group (World Bank, Washington, DC, 2018)
Over the past two decades, government-to-person cash transfer programs have become common in many countries as a means of addressing chronic poverty and insecurity for low-income and poor households. However, adequate financial knowledge and skills – the key factors of financial capability – are necessary for program beneficiaries to access and use their accounts or cash transfers effectively. Integrating financial capability development into government cash transfer programs has thus emerged as a strategic policy objective around the world. The purpose of this toolkit is to demonstrate the importance of financial capability, its benefits for social cash transfer recipients, and provide guidance on how to integrate financial education into government-led cash transfer programs. The toolkit analyzes the expected benefits from such integration, sequences a recommended roadmap of the necessary steps, and suggests a design and implementation methodology with reference to the global best practices. It provides detailed guidance on the required research, needs assessments, design aspects, pilots, evaluations, and national scale rollouts. In addition, digital finance aspects of financial education are discussed, as cash transfers are increasingly provided digitally – directly into beneficiaries’ accounts. The annexes cover the reference instruments and templates that can be used in designing and implementing integrated financial education programs.